2012
DOI: 10.1177/1073858411435706
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Polymorphisms Influence Recovery from Traumatic Brain Injury

Abstract: Traumatic brain injury (TBI) is a major public health concern in both civilian and military populations. Recently, genetics studies have begun to identify individual differences in polymorphisms that could affect recovery and outcome of cognitive and social processes following TBI. This review considers the potential for polymorphisms to influence six specific cognitive and social functions, which represent the most prominent domains of impairment following TBI: working memory, executive function, decision mak… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
28
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 35 publications
(28 citation statements)
references
References 88 publications
0
28
0
Order By: Relevance
“…1 Thus, examination of just one of these alleles in isolation (candidate gene approach) does not allow for any underlying relationships between SNPs and genes to be studied and does not take into account environmental modifications of gene expression. 2 A number of recent reviews 6,65 and studies investigating influence of other polymorphisms on outcome after TBI 66 have advocated for the examination of the interactions between a range of candidate alleles likely to contribute to cognition. Full screening of the COMT gene and other dopaminergic genes, such as dopamine receptor D2 gene or ankyrin repeat and kinase domain-containing 1, which are known to be associated with cognition, is recommended.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…1 Thus, examination of just one of these alleles in isolation (candidate gene approach) does not allow for any underlying relationships between SNPs and genes to be studied and does not take into account environmental modifications of gene expression. 2 A number of recent reviews 6,65 and studies investigating influence of other polymorphisms on outcome after TBI 66 have advocated for the examination of the interactions between a range of candidate alleles likely to contribute to cognition. Full screening of the COMT gene and other dopaminergic genes, such as dopamine receptor D2 gene or ankyrin repeat and kinase domain-containing 1, which are known to be associated with cognition, is recommended.…”
Section: Discussionmentioning
confidence: 99%
“…Full screening of the COMT gene and other dopaminergic genes, such as dopamine receptor D2 gene or ankyrin repeat and kinase domain-containing 1, which are known to be associated with cognition, is recommended. 65 Whether studying the influence of a single gene, interaction between a range of candidate alleles or multiple genes, or taking a genome-wide approach, it is clear that very large samples are required to confer sufficient statistical power to detect effects. This would perhaps be best facilitated by large-scale collaborative, multi-institutional studies.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Genetic variations of the apolipoprotein E ( APOE ) gene have been demonstrated to be associated with long-term functional outcome after TBI [911]. Polymorphisms of brain-derived neurotrophic factor ( BDNF ), monoamine oxidase A ( MAO-A ), and interleukin-6 (IL-6) have also been correlated with TBI in recent studies [1214]. Results of these studies identified several candidate genes associated with TBI, but these results are still controversial and need further validation.…”
Section: Introductionmentioning
confidence: 99%